WEB-BASED SYSTEM of DECISION SUPPORT FOR CALCULATING COMBAT AND NON-COMBAT LOSSES DURING MILITARY CAMPAIGNS IN THE MIDDLE AGES (Computer systems and information technologies, 2022)
The project is devoted to calculating the number of losses of medieval armies using artificial intelligence methods. Several possible calculation methods have been considered, and historical sources have been analyzed. The analysis of factors that affected combat and non-combat losses and the analysis of scientific and popular science literature have been carried out, and the methods proposed by specialists have been translated into the language of formulas. The process of building neural networks, selecting their architecture, searching and synthesizing data for training samples have been considered, and the process of training and verifying the obtained data have been considered. Two models of neural networks and an information model in the form of UML diagrams of the future web application have been developed. Diagrams of use cases, classes, and components for each element of the web system have been described. The models have been implemented using the modern Django framework. A full-fledged web application with microblogging has been developed and tested. The conclusions have been drawn about the efficiency and scalability of the developed system, and the functionality of the system has been demonstrated using a real historical example.The project has developed the models of an information system for analyzing the number of troops and calculating military losses of the remote past. Mathematical models have been described, historical sources have been analyzed, and detailed models of the application have been created using the UML modeling language, which allows you to understand its interface in detail at the modeling stage.Based on the data obtained in the analysis of historical literature, the neural network architectures have been developed to determine non-combat losses in the medieval army and determine combat losses based on the data on the number of each branch’s soldiers of the armed forces who were involved during the battle.Web applications for calculating combat and non-combat losses have been developed, interface design and mini-block for publishing system News have been developed either. The non-combat losses suffered by the Mongol army in the first month of the Western campaign (1236) have been calculated as the example.
Keywords: medieval military history; calculating the number of troops; Perceptron; modeling; Python; Django